1998
DOI: 10.1080/07391102.1998.10508256
|View full text |Cite
|
Sign up to set email alerts
|

Native Protein Fluctuations: The Conformational-Motion Temperature and the Inverse Correlation of Protein Flexibility with Protein Stability

Abstract: We study the fluctuations of native proteins by exact enumeration using the HP lattice model. The model fluctuations increase with temperature. We observe a low-temperature point, below which large fluctuations are frozen out. This prediction is consistent with the observation by Tilton et al. [R. F. Tilton, Jr., J. C. Dewan, and G. A. Petsko, Biochemistry 31, 2469 (1992)], that the thermal motions of ribonuclease A increase sharply above about 200 K. We also explore protein "flexibility" as defined by Debye-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 73 publications
4
84
0
1
Order By: Relevance
“…Proteins must be flexible enough to allow timely access to the many internal, microscopic and large-scale conformational fluctuations required for function, such as binding and release of a substrate from the interior of an enzyme. [58][59][60] However the propagations of large scale, collective motions that lead to protein unfolding need to be restricted. The connection between the tradeoffs of stability and function then is protein internal dynamics.…”
Section: Proteins In Solution and In The Hydrated Crystalline Statementioning
confidence: 99%
“…Proteins must be flexible enough to allow timely access to the many internal, microscopic and large-scale conformational fluctuations required for function, such as binding and release of a substrate from the interior of an enzyme. [58][59][60] However the propagations of large scale, collective motions that lead to protein unfolding need to be restricted. The connection between the tradeoffs of stability and function then is protein internal dynamics.…”
Section: Proteins In Solution and In The Hydrated Crystalline Statementioning
confidence: 99%
“…6 -8 Moreover, recently Tang and Dill have studied the temperature-induced fluctuations in the lattice model, and concluded that proteins having greater stability tend to have fewer large fluctuations, and hence lower flexibility. 9 Time-resolved fluorescence is one of the most common spectroscopic methods used to elucidate the structural and dynamic aspects of the protein structure. 10 Tryptophan residues in proteins are often used as probes to monitor the structural changes of the macromolecules in solution.…”
Section: Introductionmentioning
confidence: 99%
“…If a protein has a smooth landscape, the motions of the protein are mostly small wiggles, never deviating much from the native structure because to do so would require a high energy. But for a bumpy landscape, very non-native-like conformations can occasionally be populated under native conditions because the energies of such conformations are not much higher than those of the native molecule~Miller Tang & Dill, 1998!. During those fluctuations, protons or ligands could exchange in or out, or the protein could have other transiently different properties than the native molecule.…”
Section: Relating Thermodynamics and Kinetics: A Fluctuationdissipatimentioning
confidence: 99%